Smartphone-Based Accounting Information System Application: An Innovation Technology Solution For Startup - Lailatul Nafiisa, Birra; Jaswadi, Jaswadi; Djajanto, Ludfi (Publisher Cv. Inara, 2024)
This study aims to create an Accounting Information System (AIS) application that can be accessed using a smartphone. The object of the study is PT Orangiro Makmur Jaya (OMAJA POWER). This company is one of the startups that focuses on electrical. This type of research is Research & Development (R&D) with the Analysis, Design, Development (ADDIE) model. The results of this study are the testing of the feasibility of the application by material experts resulting in an average value of the feasibility percentage of 98% which means that the application is very feasible to implement. Next are the results of the testing of the feasibility of the application by media experts with an average value of the feasibility percentage of 100% which means that the application is very feasible to implement. Then the percentage of user satisfaction based on the Performance indicator reached 4.90%, and on the Information and data indicator 4.92%. Meanwhile, the Economic indicator obtained a percentage of 4.95%. Then on the Control and security indicator, the level of satisfaction shows a percentage of 4.94%. Next is the Efficiency indicator showing a percentage of 4.93%. The Service indicator shows a percentage of 4.92%. So, based on this percentage, it can be concluded that the existence of an AIS using the PIECES Framework is very satisfying for users.